Relative Bradycardia in Patients with Mild-to-Moderate Coronavirus Disease, Japan - Ikeuchi, Kazuhiko; Saito, Makoto; Yamamoto, Shinya; Nagai, Hiroyuki; Adachi, Eisuke (Emerging infectious diseases, 2020)
Coronavirus disease is reported to affect the cardiovascular system. We showed that relative bradycardia was a common characteristic for 54 patients with PCR-confirmed mild-to-moderate coronavirus disease in Japan. This clinical sign could help clinicians to diagnose this disease.